Desenvolvimento de hardware para análise de bioimpedância em banda larga - Souza, Anderson Francisco da Costa (2017)
The bioimpedance spectroscopy is a technique that allows the biological tissue research from its electrical properties. The applications include body composition, research in cancer cells, bioimpedance tomography and others. This paper realizes the development of a bioimpedance analyzer for frequencies between 1 kHz and 1 MHz and impedance range between 50 and 1 kΩ. The system perform the acquisition with a tetrapolar topology, which a current excitation used was ternary chirp signal. For device control and visualization of the results, a software was also developed in LabVIEW platform. As a result, the project requires a total time of 2.47 s to perform the bioimpedance measurement, however only 10 ms are used for tissue excitation, the resolution obtained was 2.44 Ω for the module and 0.29° for the phase, with errors of accuracy around 30 Ω (module) and 6 ° (phase).